РАДИАЦИОННАЯ ОЦЕНКА ПРОДУКТОВ ЖИВОТНОГО ПРОИСХОЖДЕНИЯ - А. Абжалиева; А. Алимов; Д. Касенбай; А. Узынтлеуова; Д. Төребекова (Animal Health and Biosafety, 2026)
In the context of increasing attention to radiation safety issues, monitoring the content of radionuclides in environmental objects and food products of animal origin is becoming particularly relevant. The radioecological condition of agricultural regions directly affects public health, which necessitates comprehensive studies aimed at assessing radiation background levels and the migration of radionuclides through trophic chains. The purpose of this study was to evaluate the activity of radionuclides in environmental components and cow’s milk within the territory of the Abay district.At the first stage of the study, samples of soil, water, and atmospheric precipitation were collected and analyzed. The specific activity of natural and anthropogenic radionuclides was determined using gamma spectrometric analysis. The obtained results indicate that the radiation background of the studied environmental objects does not exceed the established regulatory limits, suggesting the absence of significant radioactive contamination in the area.At the second stage, samples of cow’s milk obtained from private and farm households in the district were examined. The analysis of radionuclide content, specifically ^137Cs and ^90Sr, showed that their activity levels remain within permissible sanitary and hygienic standards. It was established that the transfer of radionuclides into milk through the feed chain is limited and does not pose a potential radiological hazard to the population. The results of the study confirm the satisfactory radioecological condition of the Abay district and the radiation safety of cow’s milk. The obtained data can be used for regional radiation monitoring and for the development of measures aimed at ensuring food safety.